2021
DOI: 10.1093/infdis/jiab117
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Birth Weight Caused by Sextuple Drug-Resistant Plasmodium falciparum Infection in Early Second Trimester

Abstract: Mutations in the Plasmodium falciparum genes Pfdhfr and Pfdhps, particularly the sextuple mutant haplotype threatens the antimalarial effectiveness of sulfadoxine-pyrimethamine as intermittent preventive treatment during pregnancy (IPTp). To explore the impact of sextuple mutant haplotype infections on outcome measures after provision of IPTp-SP, we monitored birth outcomes in women followed from prior to conception or from the first trimester until delivery. Women infected with sextuple haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A sixth mutant, dhps A581G, conveys high-grade resistance to sulfadoxine-pyrimethamine and appears to be increasing in prevalence. In Tanzania and Malawi, infection with parasites with the A581G mutation was associated with substantial decreases in birthweight compared to women with no malaria, or to women infected with parasites that lacked the mutation [52 ]. Sulfadoxine-pyrimethamine resistance has led to the search for alternative drugs or combinations.…”
Section: Malaria Prevention: Intermittent Preventive Treatmentmentioning
confidence: 99%
“…A sixth mutant, dhps A581G, conveys high-grade resistance to sulfadoxine-pyrimethamine and appears to be increasing in prevalence. In Tanzania and Malawi, infection with parasites with the A581G mutation was associated with substantial decreases in birthweight compared to women with no malaria, or to women infected with parasites that lacked the mutation [52 ]. Sulfadoxine-pyrimethamine resistance has led to the search for alternative drugs or combinations.…”
Section: Malaria Prevention: Intermittent Preventive Treatmentmentioning
confidence: 99%
“…Before the advent of the Pfdhps 431V mutation in Nigeria, East Africa witnessed a similar scenario with the emergence of the quintuple ( IRN + 437 G + 540 E ) and sextuple ( IRN + 437 G + 540 E + 581 G ) mutant haplotypes. These were associated with a reduction in the mean birth weight and other metrics of SP-IPTp failure in Tanzania [ 13 , 56 ]. Although no 540E mutation was observed in the present study, it is possible that the emerging Pfdhps 431V and its co-occurrence with 581G and 613S could lead to a higher order mutant haplotype, and this alternative sextuple mutant might compromise the chemopreventive impact of SP-IPTp in West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the prevalence of Pfdhps 431V varies across regions in Nigeria in clinical isolates collected at various respective study periods [ 13 15 ]. For instance, a low prevalence of Pfdhps 431V mutation was reported in Southwest Nigeria, whereas the prevalence in the parasite population is widespread in the Southeast and Northeast Nigeria among the samples collected about a decade ago [ 13 ]. Figures 2 and 3 give a view of the spatial distribution of Pfdhps -431V and -581G in Nigeria and neighbouring countries, using data reported in surveys conducted between 2007 and 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women were screened for malaria using malaria rapid diagnostic test kit (ParaHIT, Span Diagnostics or CareStart Malaria Pf, ACCESS BIO). Microscopy were performed on all samples, and PCR on a subset, to confirm malaria positivity [ 32 ]. Malaria patients were offered oral artemether-lumefantrine (Lumartem 20 mg/120 mg, Cipla Ltd), quinine, or artesunate injections depending on severity and GA [ 32 ].…”
Section: Methodsmentioning
confidence: 99%